Characteristics of growth and protein synthesis in skeletal muscles of normal and dystrophic chickens - Kang, Chang W.; Sunde, Milton L.; Swick, Robert W. (Biochimica et biophysica acta, 1984)
Several characteristics of cellular growth and protein synthesis were measured in vivo in the breast and leg muscles of normal (line 454) and hereditary muscular dystrophic (line 455) New Hampshire chickens at different ages. Fractional rates of protein synthesis (k s) were calculated from the rate of incorporation of labeled tyrosine administered continuously via a subcutaneous injection of an emulsion of L-[U- 14C]tyrosine in sesame oil. Only the breast muscle showed signs of gross hypertrophy. The hypertrophy involved an abnormally rapid accumulation of protein, DNA and RNA. In dystrophic chickens, k s was at least 170% of the normal rates at 2, 5 and 52 weeks. The elevated k s was presumably a reflection of the higher DNA and RNA concentrations relative to those in normal birds. Because the RNA/DNA ratio and the activities of RNA and DNA were similar to values observed in normal birds, there may be no defect in the synthesis machinery per se.